Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the given system of equations:
[tex]\[ \left\{\begin{array}{l} y = x^2 - 6x + 5 \\ y = 2x - 7 \end{array}\right. \][/tex]
we need to find the points [tex]\((x, y)\)[/tex] where the two equations intersect.
1. Step 1: Set the equations equal to each other because at the points of intersection the [tex]\(y\)[/tex]-values from both equations must be equal:
[tex]\[ x^2 - 6x + 5 = 2x - 7 \][/tex]
2. Step 2: Rearrange the equation to set it to zero:
[tex]\[ x^2 - 6x + 5 - 2x + 7 = 0 \\ x^2 - 8x + 12 = 0 \][/tex]
3. Step 3: Factor the quadratic equation:
[tex]\[ x^2 - 8x + 12 = (x - 2)(x - 6) = 0 \][/tex]
4. Step 4: Solve for [tex]\(x\)[/tex]:
[tex]\[ x - 2 = 0 \quad \text{or} \quad x - 6 = 0 \\ x = 2 \quad \text{or} \quad x = 6 \][/tex]
5. Step 5: Substitute the [tex]\(x\)[/tex]-values back into either original equation to find the corresponding [tex]\(y\)[/tex]-values. We can use the linear equation [tex]\(y = 2x - 7\)[/tex] because it is simpler:
For [tex]\(x = 2\)[/tex]:
[tex]\[ y = 2(2) - 7 = 4 - 7 = -3 \][/tex]
For [tex]\(x = 6\)[/tex]:
[tex]\[ y = 2(6) - 7 = 12 - 7 = 5 \][/tex]
6. Step 6: Write the solutions as ordered pairs and sort by the [tex]\(x\)[/tex]-values:
[tex]\[ (2, -3) \quad \text{and} \quad (6, 5) \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ ([2, 6], [-3, 5]) \][/tex]
[tex]\[ \left\{\begin{array}{l} y = x^2 - 6x + 5 \\ y = 2x - 7 \end{array}\right. \][/tex]
we need to find the points [tex]\((x, y)\)[/tex] where the two equations intersect.
1. Step 1: Set the equations equal to each other because at the points of intersection the [tex]\(y\)[/tex]-values from both equations must be equal:
[tex]\[ x^2 - 6x + 5 = 2x - 7 \][/tex]
2. Step 2: Rearrange the equation to set it to zero:
[tex]\[ x^2 - 6x + 5 - 2x + 7 = 0 \\ x^2 - 8x + 12 = 0 \][/tex]
3. Step 3: Factor the quadratic equation:
[tex]\[ x^2 - 8x + 12 = (x - 2)(x - 6) = 0 \][/tex]
4. Step 4: Solve for [tex]\(x\)[/tex]:
[tex]\[ x - 2 = 0 \quad \text{or} \quad x - 6 = 0 \\ x = 2 \quad \text{or} \quad x = 6 \][/tex]
5. Step 5: Substitute the [tex]\(x\)[/tex]-values back into either original equation to find the corresponding [tex]\(y\)[/tex]-values. We can use the linear equation [tex]\(y = 2x - 7\)[/tex] because it is simpler:
For [tex]\(x = 2\)[/tex]:
[tex]\[ y = 2(2) - 7 = 4 - 7 = -3 \][/tex]
For [tex]\(x = 6\)[/tex]:
[tex]\[ y = 2(6) - 7 = 12 - 7 = 5 \][/tex]
6. Step 6: Write the solutions as ordered pairs and sort by the [tex]\(x\)[/tex]-values:
[tex]\[ (2, -3) \quad \text{and} \quad (6, 5) \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ ([2, 6], [-3, 5]) \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.